Analyzing environmental factors for predicting the adoption of Islamic Financing Facilities among Halalcertified Companies in Malaysia / Hazalina Mat Soha ... [et al.] - Mat Soha, Hazalina; Mat Junoh, Mohd Zukime; Tunku Ahmad, Tunku Salha; Islam, Md. Aminul (UiTM Cawangan Negeri Sembilan, 2023)
This study investigates the environmental factors on the intention to adopt Islamic financing facilities among halal-certified companies in Malaysia. The research utilizes Technology, Organization, and Environmental (TOE) framework as underlying theory, with a specific focus on environmental factors. A relevant questionnaire was designed and distributed among the owners or managers of halal certified companies in Malaysia. Data from 237 halal-certified companies were collected after a simple random sampling selection. The hypotheses were tested using a Structural equation modelling with SmartPLS. The findings show that competitive pressure has a significant positive impact on the intention to adopt Islamic financing facilities, while customer pressure have no significant impact. Also, this study provides crucial insight to bank managers regarding the development of effective strategies aimed at enhancing the adoption of Islamic financing facilities among halal-certified companies